Copula and Focus Marker in Central Yorùbá Dialects - Ọláńrewájú, Emmanuel Ọmọniyì (Universitas Negeri Semarang, 2024)
This paper investigated the morpho-syntactic distribution of ‘’ni’’ in Central Yorùbá (hence, CY) dialect. Primary and secondary data were collected on CY dialects (Ifẹ̀, Ìjẹ̀ṣà, Èkìtì and Mọ̀bà) and subjected to syntactic analysis. Noam Chomsky’s Minimalist Program (MP) of generative grammar was adopted. Two allomorphs of ni identified are: li and ri. The dialects operate ‘’ni’’, ‘’li’’ and ‘’ri’’ as focus markers. These also have their variants that perform predicate function. These are referred to as copula in this paper. Both copula and focus markers are in complementary distribution. ‘’Ni’’ and ‘’li’’ are in free variation in Èkitì and Mọ́bà unlike Ifẹ̀ and Ìjẹ̀ṣa where they are in complementary distribution. Mọ̀bà dialect operates both the focus marker ‘’ri’’ and its copula variant ‘’ri’’ while other CY dialects operate ‘’ri’’ only as a copula. A focus marker is optionally dropped when used with some question nouns (QNs) in the dialects. Three syntactic distributions identified with ‘’ni’’ and its variants are: focused interrogatives, focus constructions and copula constructions. CY dialects exhibit some common features with respect to how both focus markers and copula are operated.